Single-incision bilateral laparoscopic oophorectomy - Bhandarkar, Deepraj (Medknow Publications, 2011)
Although single-incision laparoscopic surgery made an appearance on the surgical scene only recently, it is being increasingly applied in the treatment of a variety of disorders. We report single-incision bilateral laparoscopic oophorectomy and salpingooophorectomy performed in two patients who had previously undergone breast conservation surgery for early breast cancer. Each procedure was undertaken using two 5-mm and one 3-mm ports inserted through a 2-cm transverse supraumbilical incision and standard laparoscopic instruments. The operative time was 50 and 65 min respectively and the blood loss negligible. The patients were discharged 36 and 24 h after surgery, required minimal postoperative analgesia and remain well at a follow up of 19 and 17 months, respectively. With the benefit of improved cosmesis, the single-incision approach holds the potential to replace the traditional bilateral laparoscopic oophorectomy.